2022
DOI: 10.1039/d1qm01311d
|View full text |Cite
|
Sign up to set email alerts
|

New shoots from old roots: multiple stimuli-responsive properties of a common tetraphenylethene derivative

Abstract: Multiple stimuli-responsive fluorescent materials are still in high demand owing to academic significance and potential applications. Designing a novel molecule with multiple stimuli-responsive properties is a hard work due to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…S6 (ESI†), the decomposition temperature ( T d , the temperature of 5% weight loss) of this molecule was 280 °C. Compared with other similar stimuli-responsive molecules reported before, 19,44,50 the thermal stability of TDBA-SP was quite excellent, which can meet the needs of practical application. Meanwhile, the lower melting point (about 58 °C) made it is easier to process (Fig.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…S6 (ESI†), the decomposition temperature ( T d , the temperature of 5% weight loss) of this molecule was 280 °C. Compared with other similar stimuli-responsive molecules reported before, 19,44,50 the thermal stability of TDBA-SP was quite excellent, which can meet the needs of practical application. Meanwhile, the lower melting point (about 58 °C) made it is easier to process (Fig.…”
Section: Resultsmentioning
confidence: 76%
“…In particular, multi-stimuli responsive materials are of great interest to researchers. 11,[17][18][19] Compared with single stimulus responsive materials, they can provide more intuitive, multifaceted and more complete control effects. For anti-counterfeiting materials, multiple stimulus responsive materials are obviously more important.…”
Section: Introductionmentioning
confidence: 99%
“…7E). 111 As shown in Fig. 7F, the amorphous ground state 14g showed strong green emission ( λ em = 490 nm, Φ fl = 50.9%).…”
Section: Mechanochromismmentioning
confidence: 74%
“…[17][18][19] Besides, some organic systems were found to present mechanoluminescence (ML), another important type of luminescence induced by mechanical stimulation such as grinding, rubbing, or shaking. [20][21][22][23][24] Systematic studies indicated that ML was heavily related to the piezoelectric effect, in which the singlet and triplet excitons could be formed through the recombination of positive and negative charges at the broken interfaces. An ML material sensitive to mechanical force could be utilized in the applications of pressure sensors and heartbeat monitors etc.…”
Section: Introductionmentioning
confidence: 99%